Problematyka wyboru formy opodatkowania dochodów przez małe przedsiębiorstwo - Staniszewski, Waldemar (My University, 2011)
Pracę niniejszą poświęcono problematyce wyboru formy opodatkowania dochodów przez małe przedsiębiorstwo. Na podstawie analizy sytuacji dotyczącej wyboru formy opodatkowania na terenie powiatu limanowskiego podjęto próbę określenia preferencji wyboru poszczególnych form opodatkowania z punktu widzenia podatnika. Badania przeprowadzono w oparciu o dane Urzędu Skarbowego w Limanowej za lata 2004-2008. Z analizy danych Urzędu Skarbowego w Limanowej wynika, iż największą popularnością wśród podatników cieszy się opodatkowanie w formie ryczałtu od przychodów ewidencjonowanych.

This work was devoted to issues of choice of the form of taxation of profits by the small-sized enterprise. On the basis of the situation analysis of the form of taxation concerning selection on the area of the Limanowa district they made an attempt at determining preferential treatment of choice of individual forms of taxation from the point of view of the taxpayer. They conducted research based on data of the revenue office in Limanowa in the years 2004 - 2008. In Limanowa it results from the data analysis of the revenue office that taxing the lump sum on registered revenue in the form is enjoying the greatest popularity with taxpayers.
The issue of selecting income taxion forms by small companies
Keywords: działalność gospodarcza i jej formy; małe przedsiębiorstwo; formy opodatkowania (zasady ogólne, ryczałt od przychodów ewidencjonowanych, karta podatkowa, podatek liniowy); zalety i wady poszczególnych form opodatkowania; the business activity and her forms; small-sized enterprise; forms of taxation (broad principles, lump sum on registered revenue, flat rate tax, linear tax); the merits and demerits of individual forms of taxation